Guardians' Perceptions of Dogs' Welfare and Behaviors Related to Visiting the Veterinary Clinic. Issue 1 (2nd January 2017) - Mariti, Chiara; Pierantoni, Ludovica; Sighieri, Claudio; Gazzano, Angelo
Abstract : A large survey of Italian dog guardians ( n = 906) was conducted to assess dog behavior and welfare at the veterinary clinic and to investigate how guardians and veterinarians affect them. This study confirmed that the veterinary clinic is a source of stress for most dogs, who showed impaired welfare in all phases: in the waiting room, entering the examination room, on the examination table, and when approached by the vet. This study also characterizes some factors related to the guardians' and veterinarians' behavior that affect the dogs' behavior and welfare during the veterinary examination. If dogs had not been examined by a vet since puppyhood, if they did not accept treatments by their guardians, and if they were scolded when refusing a treatment, the risk for having problems with dog welfare and behavior at the veterinary clinic increased. The attention paid by the vet to the dog was found to be positively related with a good response of the dog to the vet. Prevention seems to be the key for the protection of dog welfare related to veterinary care.